PARA COMPREENDER A TRANSFORMAÇÃO DO PATRIMÔNIO COGNITIVO AGRÍCOLA E ECOLÓGICO NO FAXINAL TAQUARI DOS RIBEIROS, RIO AZUL, PARANÁ: ABORDAGENS ETNOCIENTÍFICA E GEOGRÁFICA - Silva, Andrea Aparecida Inacio da (2012)
The “faxinal” landscape is a complex system resulting from the interaction between nature and traditional rural communities that develop production practices joined to a system of knowledge and representation of landscapes. The actions, experimented practices in relationship between man and nature enable the individuals to formulating and improving knowledge, resulting from their close relationship with environment and each other, practicing, then, the territoriality in a continuous process of accumulation, elaboration and re-elaboration of knowledge. The present work aims to understand the ecological cognitive heritage setting about community planting lands in Faxinal Taquari dos Ribeiros in Rio Azul - Paraná, before and after the phenomenon of occupation of tobacco plantations in the market of Center South Region of Paraná. Starting from the set of geographical representations and from the practical systems is possible to make a inner reading of the cognitive systems from the perspective of the daily life of farmers of Faxinal. This approach leads to a comprehension of recovery schemes of territories, i.e., the collective actions in crystallized countryside. The productive practices of older farmers of Faxinal joined to their training in dealing with the land and the exchange of experience between them or their descendants have been helping to keep this praxis found in land planting of Faxinal Taquari dos Ribeiros, keeping alive the purpose in taking the sustenance from the land and keep the Faxinal alive by producing their cultivations and maintaining their vernacular knowledge in the landscape.